2005
DOI: 10.1128/aem.71.7.3889-3899.2005
|View full text |Cite
|
Sign up to set email alerts
|

Improved and Versatile Transformation System Allowing Multiple Genetic Manipulations of the Hyperthermophilic Archaeon Thermococcus kodakaraensis

Abstract: We have recently developed a gene disruption system for the hyperthermophilic archaeon Thermococcus kodakaraensis by utilizing a pyrF-deficient mutant, KU25, as a host strain and the pyrF gene as a selectable marker. To achieve multiple genetic manipulations for more advanced functional analyses of genes in vivo, it is necessary to establish multiple host-marker systems or to develop a system in which repeated utilization of one marker gene is possible. In this study, we first constructed a new host strain, KU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
212
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 203 publications
(212 citation statements)
references
References 30 publications
0
212
0
Order By: Relevance
“…There are three main factors that led to our low number of initial transformants. First, unlike Thermococcus kodakarensis and Pyrococcus furious, which display strong natural competence (Lipscomb et al, 2011;Sato et al, 2003Sato et al, , 2005, electroporation is the only effective way for the exogenous DNA to be introduced into S. islandicus strains. Most of the cells would be killed after electroporation and the relatively lower transformation efficiency [0-5 colonies (mg DNA) 21 for a circular knockout plasmid] usually result in a failure to obtain transformants, particularly when using a gene knockout plasmid for transformation (Deng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There are three main factors that led to our low number of initial transformants. First, unlike Thermococcus kodakarensis and Pyrococcus furious, which display strong natural competence (Lipscomb et al, 2011;Sato et al, 2003Sato et al, , 2005, electroporation is the only effective way for the exogenous DNA to be introduced into S. islandicus strains. Most of the cells would be killed after electroporation and the relatively lower transformation efficiency [0-5 colonies (mg DNA) 21 for a circular knockout plasmid] usually result in a failure to obtain transformants, particularly when using a gene knockout plasmid for transformation (Deng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both glycolytic (starch or maltodextrin) and gluconeogenic (peptides or pyruvate) modes of growth are observed for this archaeon, and the TGM sequences are found on most of the glycolytic and starch-utilizing gene promoters (25). The development of a gene disruption system for T. kodakaraensis (28,29) as well as the availability of genome information (30) makes this archaeon an attractive model organism for the elucidation of the physiological role of unknown gene function in Thermococcales (31)(32)(33).…”
mentioning
confidence: 99%
“…A genetic manipulation system was developed for Thermococcus kodakarensis (4), and phenotype analyses of the hef mutant strain confirmed that Hef is involved in multiple repair processes, and its especially high sensitivity to mitomycin C suggested that Hef performs a critical function in DNA interstrand cross-link repair (5). The helicase and nuclease activities of the purified T. kodakarensis Hef protein (TkoHef) for forkstructured DNA was also confirmed in vitro (5).…”
mentioning
confidence: 95%